Developmental Precursors of Relational Aggression From Late Childhood Through Adolescence. Issue 1 (13th October 2018) - Aizpitarte, Alazne; Atherton, Olivia E.; Zheng, Lucy R.; Alonso‐Arbiol, Itziar; Robins, Richard W.
Abstract : Relational aggression—a psychological form of aggression—has numerous negative consequences for physical and emotional health. However, little is known about the risk factors that lead youth to engage in relational aggression. Using multimethod data from a longitudinal research of 674 Mexican‐origin youth, this study examined the influence of parents, siblings, and peers on the development of relational aggression. Increases in relational aggression from age 10 to 16 were associated with: (a) low levels of parental monitoring and (b) increased association with deviant peers and siblings. These results held across gender and nativity status. The findings suggest that multiple socialization agents contribute to the development of relational aggression. We discuss the practical implications for reducing relational aggression during adolescence.